Application of interior boundary conditions in unsteady flow computation - Nguyen Cao Don; Kubo, Naritaka; Huynh, Ngoc Phien; Sutat Weesakul; The Royal Danish Government; DANIDA (Bangkok : Asian Institute of Technology, 1998)
A mathematical model concerning both the representation of the physical reality and the numerical method is developed to analyze transient state flow in open channels caused by flow and or stage changes with time and space. The problem also related to free-surface unsteady flow in natural and artificial channels in which interior boundaries are convenient tools to represent various kinds of structures and facilities in waterway. Firstly, the methods of numerical integration with simulation of unsteady flow are reviewed. Secondly, applying the numerical simulation and combining the interior boundaries, an Unsteady Flow Model dealing with a more complicated structures is developed. Thirdly, the newly developed model is formulated to express the structure of the simple Tank model. The model is then applied to the open channels system. The applicability of the model is tested for a river basin channel network system. It is shown that the hydraulic model can apply to any open channels system. Furthermore, it is able to express precisely a complex structure like the Tank Model with the help of using and combining interior boundaries.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering. School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Hydraulics -- Mathematical models